VALIDITY AND PRACTICALITY TEST OF CREATIVE ADVERTISING INSPIRATION BOARD LEARNING MEDIA BASED ON GOOGLE SITES IN LEARNING ADVERTISING TEXTS IN GRADE VIII - Jasika Putri Novela; Harry Andheska; Fabio Testy Arince Loren; Isnaini Leo Shanty; Legi Elfitra; Suhardi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to examine the validity and practicality of the Creative Advertising Inspiration Board learning media based on Google Sites in teaching advertising texts for eighth-grade junior high school students. The research employed a Research and Development (R&D) method using a 4D model limited to the defining, designing, and developing stages. The research subjects consisted of media experts, material experts, and eighth-grade students. Data were collected through interviews and questionnaires, while data analysis was conducted using descriptive quantitative techniques. The results showed that the media validity assessment by media experts reached 84%, categorized as very valid, while material expert validation achieved 90%, also categorized as very valid. The practicality test in a small group obtained a percentage of 80.20% with a practical category, whereas the large-group practicality test reached 86.40%, categorized as very practical. Based on these findings, the Google Sites–based Creative Advertising Inspiration Board is considered valid and practical as a supporting learning medium for advertising text instruction in junior high schools.